Damned for their difference : the cultural construction of deaf people as "disabled" : a sociological history - Branson, Jan; Miller, Don (Washington, D.C. : Gallaudet, 2002)
Lit. opg.; Reg.
Includes bibliographical references and index.
Keywords: Deaf; Deaf -- Great Britain